Mapping Emerging Themes in Sustainability Accounting: A Systematic Literature Review - Darmawati, Cut; Miraza, Chairanisa Natasha; Adnan, Muhammad Ichsan (Universitas Teuku Umar, 2025)
Sustainability accounting has developed into a critical field of study that supports responsible business practices in relation to environmental, social, and governance (ESG) dimensions. Although the number of publications addressing this topic has grown considerably in recent years, limited research has systematically identified the main themes and variables most frequently discussed in sustainability accounting literature. This study aims to map the emerging themes in sustainability accounting through a systematic literature review combined with content analysis. Data were obtained from the Scopus database using the keywords “sustainability accounting” and “green accounting.” The inclusion criteria required that articles be published in Scopus-indexed journals, written in English, issued between 2021 and 2024, and explicitly focused on sustainability accounting or ESG reporting. From an initial collection of 71 documents, 42 articles met the criteria and were analyzed. The findings indicate that dominant thematic categories include sustainability disclosure, green accounting, ESG reporting, environmental information quality, and the financial materiality of sustainability issues. In addition, subtopics such as green regulation, voluntary reporting systems, and the linkage between financial and environmental performance are frequently explored. The study also reveals variations in methodological approaches and the geographical distribution of research. These findings contribute to a more comprehensive understanding of the knowledge structure in sustainability accounting and provide a foundation for future research directions in this domain.